Inhibitory activity of glass-ionomer cements on cariogenic bacteria - Duque, C.; Negrini, T. C.; Hebling, J.; Spolidório, Denise Madalena Palomari [UNESP] (My University, 2005)
This study evaluated the antibacterial activity of the glass-ionomer cements Vitrebond (3M ESPE), Ketac Molar (3M ESPE) and Fuji IX (GC America) against S mutans, S sobrinus, L acidophilus and A viscosus, using the agar diffusion test. Inocula were obtained by the seed of indicators cultures in BHI broth incubated at 37°C for 24 hours. Base layers containing 15 mL of BHI agar and 300 μL of each bacteria suspension were prepared in Petri dishes. Six wells measuring 4 mm in diameter were made in each plate and completely filled with one of the testing materials. A 0.2% chlorhexidine solution applied in round filter papers was used as control. Tests were performed 12 times for each material and bacteria strain. After incubation of the plates at 37°C for 24 hours, the zones of bacterial growth inhibition around the wells were measured. Overall, the results showed the following sequence of antibacterial activity: Vitrebond (despite the activation mode) > 0.2% chlorhexidine > Ketac Molar > Fuji IX, according to Kruskal-Wallis and Mann-Whitney statistical tests. This study confirmed significant antibacterial activity for two conventional glass-ionomers and one resin-modified glass-ionomer material. The resin-modified glass-ionomer cement Vitrebond, regardless of the activation mode, presented the best antibacterial activity against S mutans and S sobrinus. The antibacterial activity against A viscosus for Vitrebond was similar to 0.2% chlorhexidine, while light activation reduced its antibacterial activity against L acidophilus. ©Operative Dentistry, 2005.
Keywords: 2 hydroxyethyl methacrylate; fuji IX; glass ionomer; ketac molar; ketac-molar; methacrylic acid derivative; topical antiinfective agent; Vitrabond; Actinomyces viscosus; chemistry; comparative study; dental caries; drug effect; Lactobacillus acidophilus; microbial viability; microbiology; nonparametric test; Streptococcus mutans; Streptococcus sobrinus; Anti-Infective Agents, Local; Dental Caries; Glass Ionomer Cements; Methacrylates; Microbial Viability; Statistics, Nonparametric